VARIABLE DNA SEQUENCE OF THE pMGA GENE IN Mycoplasma gallisepticum - Tamara MILOŠEVIČ BERLIČ; D. BENČINA; P. DOVČ (Acta Agriculturae Slovenica)
Specific fragments of Mycoplasma gallisepticum genomic DNA, representing different regions of pMGA1.1 and pMGA1.2 genes, were amplified by Polymerase Chain Reaction (PCR). Using sequence analysis of pMGA terminal domains, differences in nucleotide sequences among strains of M. gallisepticum were identified. Restriction analysis revealed polymorphism at the 5? -end of the pMGA coding region. By means of sequence analysis it was established that the most variable part of pMGA sequence was the 5? -end of the pMGA gene, the region coding amino-terminal part of pMGA protein, while the 3? -end of the gene was conserved among various M. gallisepticum strains analysed. In some strains insertions or deletions were found that indicate the diversity of the pMGA gene family and might be related to the variable expression of the pMGA gene family. Changes in nucleotide sequences of the pMGA genes were also found within isogenic lineages. Genotypic variability is also confirmed by results of the study of the gene product expression.